Avaliação e otimização da etapa de moagem primária e remoagem de um minério de ferro itabirítico da região de Morro do Pilar - Kelly Cristina Ferreira (2016)
Determining energy consumption and the mill scale-up has been target of the scientists since the XIX century, starting with Rittinger and Kick. Recently, techniques involving mathematical modeling have been successfully applied to both processes. The material for our study is an itabirite iron ore from Morro do Pilar region, that was ground in a closed ball mill circuit using hidrocyclones. The primary grinding and theregrinding stages were the focus of our study. Several methodologies have been used in order to determine the primary grindingenergy consumption, as well as determining the selection and breakage parameters for different grinding media and the optimization of the pre-designed circuit. The results indicated small specific energy consumption for the iron ore used in our study. Besides, the Bond Work Index in the absence of the initial fines presented values closer to those achieved in the simulation. For the regrinding stage, Dondas empirical method was applied and the breakage and selection functions were determined for distinct grinding media as optimization of the pre-designed circuit. For the regrinding circuit, the energy consumption using Dondas method yielded higher values than those from the simulation.